MANAGEMENT OF BEHAVIOR PROBLEMS AT SCHOOL - Bambang Afriadi (LPPM Universitas Negeri Jakarta, 2022)
Behavior problems become essential to be discussed from time to time, and every era has different challenges in terms of handling. This article focuses on behavioral problems in schools. This paper will evaluate several studies, all of which are based on a google.com search and will be presented in order with their sources. Scientific studies, building a trusted website, and https://trends.google.co.id/trend collecting information. It is essential to develop character on behavioral difficulties in this school and how we can work together to find the best solutions for this fast-paced era. This report will serve as a springboard for future research on school behavior issues